Local Wisdom Based on Indigenous Cultural Values of the Karo Batak Community - Bancin, M. Rizky Alqodry; Ananda, Faisar; Iwan, Iwan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This research aims to describe the value-based local wisdom of the Karo Batak community, especially in the customary inheritance law system. This research uses a qualitative approach with a case study method. Data were obtained from various sources, including literature, interviews with traditional leaders, and direct observation of inheritance law practices in the Karo Batak community. Data collection techniques included in-depth interviews, document studies, and participatory observation. Data analysis was conducted through data reduction, data presentation, and inductive inference. The results showed that the Karo Batak customary inheritance law is based on a patrilineal system, where the eldest son is the main heir. However, in certain situations, women also have the right to inherit property, especially if there are no sons in the family. Inherited property, especially land or hereditary property, tends to be passed down patrilineally to maintain the continuity of the lineage. In addition, the role of ancestors is very influential in the process of distributing inheritance, with strong customary mechanisms to resolve conflicts. The conclusion of this study shows that although Batak Karo customary inheritance law is still practiced, modernization has brought challenges and adaptations to this system. Urbanization, education, and the influence of national laws have led some families to adopt a combination of customary and state laws to suit social and economic needs. Therefore, policies that accommodate cultural values and aspects of justice in inheritance practices in the Karo Batak community are recommended to remain relevant to the times.